Imagined communities : reflections on the origin and spread of nationalism - Anderson, Benedict (Verso, 2006)
What makes people love and die for nations, as well as hate and kill in their name? While many studies have been written on nationalist political movements, the sense of nationality - the personal and cultural feeling of belonging to a nation - has not received proportionate attention. In this widely acclaimed work, Benedict Anderson examines the creation and function of the "imagined communities" of nationality and the way these communities were in part created by the growth of the nation-state, the interaction between capitalism and printing and the birth of vernacular languages in early modern Europe.